Potential of desiccation-tolerant plant growth-promoting rhizobacteria in growth augmentation of wheat (Triticum aestivum L.) under drought stress - Shankar, Ajay; Prasad, Vishal (Frontiers in Microbiology, 2023)
Wheat (Triticum aestivum L.) yield and physiology is adversely affected due to limited water availability. However desiccation tolerant plant growth promoting rhizobacteria (DT-PGPR) are potential candidates to overcome the negative impacts of water stress. In present work a total of 164 rhizobacterial isolates were screened for desiccation tolerance up to -0.73MPa osmotic pressure, of them five isolates exhibited growth and expression of plant growth properties under influence of desiccation stress of -0.73MPa. These five isolates were identified as Enterobacter cloacae BHUAS1, Bacillus cereus BHUAS2, Bacillus megaterium BHUIESDAS3, Bacillus megaterium BHUIESDAS4 and Bacillus megaterium BHUIESDAS5. All five isolates exhibited plant growth promoting properties and production of exopolysaccharide (EPS) under impact of desiccation stress. Further in pot experiment on wheat (variety HUW-234) having inoculation with the isolates Enterobacter cloacae BHUAS1, Bacillus cereus BHUAS and Bacillus megaterium BHUIESDAS3 exhibited positive influence on growth of wheat under condition of water stress. A significant improvement in plant height, root length, biomass, chlorophyll and carotenoid content, membrane stability index (MSI), leaf relative water content (RWC), total soluble sugar, total phenol, proline, total soluble protein, were recorded under limited water induced drought stress in treated plant as compare to non-treated. Moreover plants, treated with Enterobacter cloacae BHUAS1, Bacillus cereus BHUAS and Bacillus megaterium BHUIESDAS3 depicted improvement in enzymatic activities of several anti-oxidative enzymes like guaiacol peroxidase (POD), catalase (CAT) and ascorbate peroxidase (APX). Beside this significant decrease in electrolyte leakage, H2O2 and malondialdehyde (MDA) content were also recorded in treated plants. From the results obtained it is evident that E. cloacae BHUAS1, B. megaterium BHUIESDAS3 and B. cereus are the potential DT-PGPR having capability to endure growth and yield and alleviating deleterious effect of water stress in wheat.